2013
DOI: 10.1254/jphs.13128sc
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of TRPA1 as a Downstream Signal of Proteinase-Activated Receptor-2 to Pancreatic Pain

Abstract: Abstract. We examined if TRPA1, like TRPV1, contributes to pancreatic nociceptor excitation following proteinase-activated receptor-2 (PAR2) stimulation and to pancreatitis-related pain in mice. A PAR2-activating peptide, infused into the pancreatic duct, caused spinal Fos expression, which was prevented by AP18, a TRPA1 inhibitor. Repeated administration of cerulein caused referred hyperalgesia accompanying pancreatitis, which was reversed by SB366791, a TRPV1 inhibitor, but not AP18. AP18, administered in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Moreover, the first-generation TRPV1 antagonist, capsazepine, diminished discomfort to colorectal distension in mice (Sugiura et al, 2007), similar to the decrease seen in TRPV1-null animals (Jones et al, 2005a). Interestingly, TRPV1 and TRPA1 antagonists synergistically attenuate caerulein-induced pain behavior and pancreatic inflammation (Schwartz et al, 2011;Terada et al, 2013) and prevent the transition from acute to chronic pain during experimental pancreatitis (Schwartz et al, 2013); after this transition, TRP antagonism is ineffective. Alcohol abuse is a well known cause of acute pancreatitis.…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, the first-generation TRPV1 antagonist, capsazepine, diminished discomfort to colorectal distension in mice (Sugiura et al, 2007), similar to the decrease seen in TRPV1-null animals (Jones et al, 2005a). Interestingly, TRPV1 and TRPA1 antagonists synergistically attenuate caerulein-induced pain behavior and pancreatic inflammation (Schwartz et al, 2011;Terada et al, 2013) and prevent the transition from acute to chronic pain during experimental pancreatitis (Schwartz et al, 2013); after this transition, TRP antagonism is ineffective. Alcohol abuse is a well known cause of acute pancreatitis.…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 72%
“…Both proteins are colocalized in DRG. Stimulation of PAR-2 activates TRPA1 (Dai et al, 2007;Terada et al, 2013). As detailed later, there is evidence that TRPV1 and TRPA1 are not only coexpressed but also functionally coupled in DRG neurons, where they may also form functional heterotetramers.…”
Section: +mentioning
confidence: 84%
“…In the non-histaminergic pathways the key second messenger role is played by transient receptor potential cation channel, subfamily A, member 1 (TRPA1), a downstream target of proteinase-associated receptor 2 (PAR) and Mas-related G-protein coupled receptor member Gsignalling (Mrgpr) (48)(49)(50). TRPA1 appears to be crucial, not only in conveying chronic itch sensation, but also in processes such as neurogenic inflammation, epidermal hyperplasia and altered gene expression in sensory nerves, which frequently accompany chronic itch conditions (48,51).…”
Section: Defining Histamine-independent Itchmentioning
confidence: 99%
“…It has been reported that TRPA1 is sensitized by proteinase-activated receptor-2 (PAR2) activation, contributing to inflammatory pain (Dai et al 2007). We have provided evidence that pharmacological inhibition of TRPA1 prevents the spinal Fos expression following infusion of SLIGRL-NH 2 , a PAR2-activating peptide, into the pancreatic duct, suggesting the pronociceptive role of TRPA1 as a downstream signal of PAR2 activation in the pancreatic nociceptors (Terada et al 2013). Most interestingly, it has been reported that NaHS evokes a time-and concentration-dependent increase in cytosolic calcium concentration in TRPA1-transfected cells (Streng et al 2008) and that NaHS induces calcium influx and inward currents in rat DRG cells, an effect inhibited by a TRPA1 antagonist (Miyamoto et al 2011;Ogawa et al 2012).…”
Section: 2mentioning
confidence: 93%